Systemic Functional Grammar Analysis on Igor’s Utterances Portraying His Ideology in Coelho’s The Winner Stands Alone - Soedjarwo, Gabriella Novianty (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2024)
Someone’s ideology can be manifested through one’s language. The language one uses to talk about himself or other can give the picture on how one sees oneself and one’s surrounding. There might be an argument that the use of language is the unconscious product. However, based on systemic functional grammar (SFG) theory, that unconscious language can be analysed from the structure to figure out the ideology of the user. This study took the novel written by Paulo Coelho entitled The Winner Stands Alone to analyse how the language used by the main character, Igor Malev, to show his ideology. There are 660 data taken from Igor’s dialogues and monologues to be analysed using SFG theory proposed by Halliday. From the analysis, this study found out that Igor shows and perceives himself as a doer, carrier, senser, existent, sayer, and behaver. It means he truly manifested his ideology as a winner and resistant in this materialistic world and he means it. He puts every thought into an action. To put simply he is a man of his word. Keyword: choice of word, ideational metafunction, ideology, interpersonal metafunction, textual metafunction